(3QSGdI aj CaVdjI GdJSHjM aj GdQcYJjf GdCNjQJjfs ((3MSjf Hf ZGfe Hf Ydi Hf YHO Gddg Hf Ydi Hf YHO Gddg Hf MHjH GdJdGOi GdHMQGfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg hGdUdGI Ydi SjOfG eMeO hBdg aEfi deG cJHJ QSGdI dWjaI ai CaVdjI GdJSHjM ai GdQcYJjf GdCNjQJjf Ydi GdbQGAI s
(3BNQgG (B:s
(3adG jSde ef GdNdGa HNdGa GdJSHjMGJ GdCKfi YTQI aEfgG eLRjg ELeGYkG hdjcf gPG BNQ eG fedjg ai gPg GdebGhdg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(398) s
Keywords: (3GdeLGejYs